PERAN AKUNTANSI MANAJEMEN DI ERA DIGITAL: TINJAUAN SISTEMATIS DAMPAK BIG DATA DAN KECERDASAN BUATAN - Putri, Khofifah Amelia; Nawangsari, Ajeng Tita (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to synthesise existing literature to map the impact of Big Data and Artificial Intelligence (AI) on the functions and roles of management accounting in the digital era. This study uses a qualitative approach with a Systematic Literature Review (SLR) method, collecting data from scientific articles published on Google Scholar between 2018 and 2025. The review results show that the integration of AI and Big Data has a significant impact on three main management accounting techniques: 1) Budgeting: AI enables more accurate forecasting, real-time cost monitoring and rapid corrective action. 2) Cost Analysis: Big Data transforms cost control from reactive to predictive and real-time, facilitating the identification of waste and optimising processes. 3) Performance Measurement: AI-based automation improves the accuracy and efficiency of financial reporting and supports sustainable decision-making. These developments are also transforming the role of management accountants from mere "number crunchers" to "strategic analysts" who interpret AI output for strategic recommendations. However, implementation faces challenges such as the need for significant IT infrastructure investment, the need for human resources skills in data analysis, and data security and privacy issues. Nevertheless, the strategic opportunities offered, such as increased operational efficiency and contribution to the Sustainable Development Goals (SDGs), are far greater.